Nanocrystalline (NixCo(1-x))3(PO4)2@FeSe2/NF as a promising OER electrocatalyst for alkaline water electrolysis - Christi, Darren Sebastian; Selvaraj, Kaliaperumal (International Journal of Hydrogen Energy, 2024)
Affordable and sustainable hydrogen production is the need of the hour owing to the mounting global pursuit for the hydrogen economy. Water splitting is the premier go -to method to produce green hydrogen at a larger scale in which the half -cell Oxygen Evolution Reaction (OER) demands a larger amount of energy expenditure due to its sluggish kinetics. Hence, designing an efficient OER electrocatalyst, especially for alkaline water electrolysis that offers alternatives to the usage of precious group metals is a pressing priority. Herein, we report a novel nanocrystalline electrocatalyst consisting of two components, namely cobalt nickel phosphate and iron diselenide synthesised via a two-step electrodeposition at room temperature. The combination of the two components on the porous nickel foam substrate exhibits an overpotential of 272 mV at 100 mA/cm2 in 1 M KOH showing a low Tafel slope of a mere 38 mV/dec with appreciable retention even after 24 h of stability test at a relatively higher current density. The surface reconstruction that occurs when FeSe2 is electrodeposited on (Ni0.35Co0.65)3(PO4)2@NF and the synergy between the two components is the primary reason for the improved performance. Thus, this work highlights the ambient synthesis of a highly durable earth -abundant metal -based electrocatalyst which exceeds the performance of the standard Ru/C by a decent margin.
Keywords: Alkaline Water Electrolysis; Ambient synthesis; Electrodeposition; Non-PGM based Electrocatalyst; OER

Composite Sn-Fe oxide as a compatible OER electrocatalyst for electrochemical alkaline water electrolysis - Velluva, Abhijai; Christi, Darren Sebastian; Selvaraj, Kaliaperumal (Journal of Physical Chemistry C, 2026)
Green hydrogen production through electrochemical water splitting is one of the optimal replacements for conventional fossil fuel energy sources. The development of highly active and electrochemically stable non-noble-metal electrocatalysts for the sluggish oxygen evolution reaction (OER) is considered to be an important step in decreasing the energy requirement during alkaline water electrolysis. Herein, we report a Sn-doped FeOx composite (SnFeOx) powder, which could be synthesized through a single-step hydrothermal method and is reported for the first time for OER during electrochemical water electrolysis. SnFeOx exhibits a low eta(100) (overpotential at 100 mA cm(-2) current density) value of 288 mV and a good Tafel slope of 35 mV dec(-1) in 1 M KOH, which surpasses the performance of standard non-PGM OER catalysts. A long-durability test at a higher current density of 100 mA cm(-2) for 50 h reveals the excellent activity retention of SnFeOx (>99%). The suitability of SnFeOx for full-water splitting was tested with Pt/C as a cathode electrode, and Pt/C/NF||SnFeOx/NF exhibited a lower eta(10) value of 1.56 V that is superior to Pt/C/NF||Ru/C/NF (1.59 V) with more than 99% retention at a current density of 10 mA cm(-2) for 50 h. The more favorable OER performance of SnFeOx compared to FeOx can be attributed to the successful Sn4+ doping along with increased oxygen defective sites and larger electrochemical surface area.